Utilization of textile waste (batik remnants) for womens’ wear in Yogyakarta, Indonesia - . Novita (Syiah Kuala University, 2012)
Innovation in the art of Indonesian batik making has triggered a larger consumption of the material for both formal and informal events. Along with the development of the art, batik has become a trend with a new decorative look that is unique, interesting and varied. Lately, indulgence in the use of batik in Yogyakarta has led to increased waste in the form of the remnants. Batik remnants in Yogyakarta that continue to accumulate and not used will have a negative impact and cause environmental pollution. The purpose of this research is to build an innovative application on the utilization of industrial wastes that is the recycling of batik remnants into products of economic value. It is expected that utilizing batik remnants can produce creative and innovative womens’ wear. The objectives are to create a number of artistic designs from batik remnants and at the same time save the environment. A total of four contemporary womens’ wear from batik remnants produced into prototypes. With creativity, innovation and exploration, batik remnants in Yogyakarta which are no longer used can be recycled into womens’ wear, which are high in economic value, and at the same time can help reduce environmental pollution